Integrative population pharmacokinetic/pharmacodynamic analysis of nemonoxacin capsule in Chinese patients with community-acquired pneumonia - Chen, Yuancheng; Wu, Xiaojie; Tsai, Chengyuan; Chang, Liwen; Yu, Jicheng; Cao, Guoying; Guo, Beining; Shi, Yaoguo; Zhu, Demei; Hu, Fupin; Yuan, Jinyi; Liu, Yang; et al. (Frontiers in Pharmacology, 2023)
Nemonoxacin is an innovative quinolone antibiotic for treatment of community-acquired pneumonia (CAP). As more data are available from clinical studies, it is necessary to perform an integrative pharmacokinetic/pharmacodynamic (PK/PD) analysis to support and justify the optimal dosing regimen of nemonoxacin in clinical practice. For this purpose, we developed a population PK model using non-linear mixed effect model based on the data of 195 Chinese subjects receiving nemonoxacin in phase I to III clinical trials. The base model was a standard two-compartment PK model defined by clearance (12 L/h) and central volume of distribution (86 L). Covariates included creatinine clearance (CLcr), body weight (BW), sex, disease status and food. Compared to the subject with BW 60kg, Cmax and AUC0-24,ss reduced by 24% and 19% in the subject with BW 80kg, respectively. Compared to the subject with CLcr 150mL/min, AUC0-24,ss and T1/2 increased by 28% and 24%, respectively in the subject with CLcr 30mL/min. Compared to the fasted status, Tmax of nemonoxacin increased by 1.2h in the subject with fed status. Effects of sex and disease status on PK parameters were small (change of PK parameters ≤ 19%). AUC0-24/MIC and %T>MIC were identified as the optimal PK/PD indices for predicting clinical efficacy. The AUC0-24/MIC target was 63.3, 97.8, and 115.7 against Streptococcus pneumoniae, Staphylococcus aureus and Haemophilus influenzae, respectively. The %T>MIC target was 7.96% against Klebsiella pneumoniae. Monte Carlo simulation showed that treatment with nemonoxacin 500 mg q24h could attain a PK/PD cutoff value higher than the MIC90 against S. pneumoniae and S. aureus. The corresponding cumulative fraction of response (CFR) was greater than 93%, while nemonoxacin 750 mg q24h would provide higher PK/PD cutoff value against Haemophilus parainfluenzae, and higher CFR (83%) than 500 mg q24h. Integrative PK/PD analysis justifies the reliable clinical and microbiological efficacy of nemonoxacin 500 mg q24h in treating CAP caused by S. pneumoniae, S. aureus and K. pneumoniae, irrespective of patient sex, mild renal impairment, empty stomach or not. However, nemonoxacin 750 mg q24h would provide better efficacy than 500 mg q24h for the CAP caused by H. parainfluenzae in terms of CFR.